(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
The paper presents two structural solutions for the high-rise building pile foundation where stylobate and high-altitude parts are not separated by a contraction joint studying results. The main difference between these structural solutions is in the use of piles of different lengths: in the first version all piles have the same length (implemented in practice) and the second version (perspective) is use of different lengths of piles and their support various engineering-geological elements (EGE): the longer piles support by stronger EGE under the altitude part and the shorter piles support by weaker EGE under the stylobate part. In calculations of the adopted versions piles tests results and geodetic observations have been considered for the used calculation methods verification